Hydrogen Fuel: A Global Concern, Policies, Future & Its Overall Impact on Prosperous Nepal - Poudel, D. R.; Khatri, G. G.; Kaphle, G. C. (Journal of Lumbini Engineering College, 2024)
There is an urgent need to find viable ways to achieve zero-emission energy feasibility due to the significant increase in environmental pollution and global warming caused by uncontrolled fossil fuel consumption over the last decade. The recent advancements in renewable energy and electric vehicles highlight the potential of policy and technology to develop global clean energy industries. Hydrogen could be a leading solution for storing energy from renewable. It has the potential to transport energy over long distances from regions with abundant energy resources to energy crisis areas. Hence, it is a good time to explore the potential of green hydrogen in a sustainable energy platform.